2018
DOI: 10.3847/1538-4357/aaa7f0
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Strong Balmer Line Absorption in Two Luminous LoBAL Quasars at z ∼ 1.5

Abstract: We present the discovery of strong Balmer line absorption in Hα to Hγ in two luminous lowionization broad absorption line quasars (LoBAL QSOs) at z ∼ 1.5, with black hole masses around 10 10 M ⊙ from near-IR spectroscopy. There are only two previously known quasars at z > 1.0 showing Balmer line absorption. SDSS J1019+0225 shows blueshifted absorption by ∼ 1400 km s −1 with an Hα rest-frame equivalent width of 13Å. In SDSS J0859+4239 we find redshifted absorption by ∼ 500 km s −1 with an Hα rest-frame equivale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
(97 reference statements)
1
12
0
Order By: Relevance
“…In contrast, previous BAL studies only found a small number (FeLo)BALQs with Ca II BAL features (e.g., Boksenberg et al 1977;Arav et al 2001;Hall et al 2003). Moreover, Balmer absorption lines have been observed in only a small number of FeLoBALQs (e.g., Hall 2007;Shi et al 2016;Schulze et al 2018). That is maybe because there has been no systematic study of FeLoBALQs prior to this work.…”
Section: Ca II He I* and Balmer Absorption Linesmentioning
confidence: 58%
“…In contrast, previous BAL studies only found a small number (FeLo)BALQs with Ca II BAL features (e.g., Boksenberg et al 1977;Arav et al 2001;Hall et al 2003). Moreover, Balmer absorption lines have been observed in only a small number of FeLoBALQs (e.g., Hall 2007;Shi et al 2016;Schulze et al 2018). That is maybe because there has been no systematic study of FeLoBALQs prior to this work.…”
Section: Ca II He I* and Balmer Absorption Linesmentioning
confidence: 58%
“…Currently, there are only a handful of BALQSOs that exhibit hydrogen Balmer absorption lines (e.g. Aoki 2010;Ji et al 2012;Zhang et al 2015;Shi et al 2016;Sun et al 2017;Schulze et al 2018) Although Balmer absorption lines are often seen in galaxy spectra, it is unlikely that the ones we see in AT2018zr are due to intervening galaxies or clouds because of the following reasons. First, high-ionization absorption troughs are detected at the same velocities as the H Balmer absorption lines, suggesting a dynamical association between them.…”
Section: High Velocity Transient Bal Systemmentioning
confidence: 99%
“…Kaspi et al 2005; Bentz et al 2009), this method allows an estimate of the mass of the SMBH, with a typical uncertainty of ∼0.3 dex. While the broad Hβ line is generally considered as the most reliable black hole mass estimator, the Mg ii line has also been shown to provide robust black hole masses (McGill et al 2008; Trakhtenbrot & Netzer 2012; Mejía-Restrepo et al 2016; Woo et al 2018;Schulze et al 2018). Since Hβ is not available for our sources, we base our black hole mass estimates on Mg ii.…”
mentioning
confidence: 99%